Reply to "Comments on 'The Quaternion LMS Algorithm for Adaptive Filtering of Hypercomplex Processes'" - Mandic, Danilo; Took, Clive Cheong (IEEE transactions on signal processing, 2019)
This is a rebuttal on the correspondence article on "Comments on The Quaternion LMS Algorithm for Adaptive Filtering of Hypercomplex Processes", T-SP-23558-2018.